Sex differences in auditory processing vary across estrous cycle - Jennifer Krizman (Nature Portfolio, 2021)
Abstract In humans, females process a sound’s harmonics more robustly than males. As estrogen regulates auditory plasticity in a sex-specific manner in seasonally breeding animals, estrogen signaling is one hypothesized mechanism for this difference in humans. To investigate whether sex differences in harmonic encoding vary similarly across the reproductive cycle of mammals, we recorded frequency-following responses (FFRs) to a complex sound in male and female rats. Female FFRs were collected during both low and high levels of circulating estrogen during the estrous cycle. Overall, female rodents had larger harmonic encoding than male rodents, and greater harmonic strength was seen during periods of greater estrogen production in the females. These results argue that hormonal differences, specifically estrogen, underlie sex differences in harmonic encoding in rodents and suggest that a similar mechanism may underlie differences seen in humans.